Supply of rubber wood log in Malaysia - A. W., Noraida; Abdul Samad, Abdul Rahim (Asian Economic and Social Society, 2014)
Issue on shortage of raw material for wood processing solved by discovery of rubber wood log as one of the substitutes the natural log. This paper examines the supply of rubber wood log in Malaysia. We employ ARDL Bound Approach Test and time series data from 1980 to 2010 which represented the whole Malaysia are used to achieve the established objectives. The result shown, in the long run harvested area and wages have 1% and 10% significant level respectively. While in the short run, there was only harvested area having an impact with 1% significant level. This result indicates that, the harvested area become the most impact towards supply of rubber wood log either in short run or in the long run. While wages as input cost gave less impact in another word it become unburden to the producers.